Workers without borders? Culture, migration and the political limits to globalization - Sanjay Jain; Sumon Majumdar; Sharun Mukand (Queen's University, Department of Economics, 2009)
This paper examines the role of cultural factors in driving the politics and shape of migration policy. We show that there exists a broad political failure that results in inefficiently high barriers restricting the import of temporary foreign workers and also admitting an inefficiently large number of permanent migrants, but not enough to fill any labor shortage in the economy. We show that countries that are poor at cultural assimilation are better positioned to take advantage of short-term foreign worker programs than more culturally diverse and tolerant countries. A striking implication is that relaxing restrictions on the mobility of migrant workers across employers has the potential to raise host country welfare even though it increases migrant wages and lowers individual firm's profits. We also demonstrate the existence of multiple equilibria: some countries have mostly temporary migration programs and see a low degree of cultural assimilation by the migrants, while other countries rely more on permanent migrants and see much more assimilation.
Keywords: D72; F22; J61; 330; international migration; political economy; cultural heterogeneity; temporary workers; Globalisierung; Internationale Arbeitsmobilität; Leiharbeit; Kulturelle Beziehungen; Migrationspolitik; Wohlfahrtsanalyse